Harmonisasi Perbedaan Pandangan Masyarakat dalam Interaksi Gender pada Hadis al-Muá¹£Äfaá¸¥aá¸¥ - Akbar, Raabiul; Zainuddin, Fathul Muin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
Differences in the interpretation of Islamic teachings regarding gender interactions often lead to diverse perspectives within society. Some adopt a conservative approach that avoids physical contact and limits social interactions, while others take a more inclusive stance, encouraging respectful interactions between men and women. This study aims to explore these differing perspectives, focusing on the tradition of al-Muṣāfaḥaḥ (handshaking), and seeks a solution for harmonizing these differences in social life. This research employs a qualitative method with content analysis of various secondary sources, such as books, theses, dissertations, and academic journals. The study reveals that conservative views emphasize the importance of maintaining modesty and avoiding potential temptations, while inclusive perspectives focus on the context of interactions and the intentions behind actions. The findings indicate that harmonization between these two views is essential to create a more cohesive society, where gender interactions can align with Islamic values and the demands of modern society. In conclusion, harmonizing these views not only fosters social cohesion but also strengthens ethical values within the community.